Jack and the beanstalk: favourite tales - Daly, Audrey; Salisbury, Martin (Ladybird Loughborough, 1994)
A boy climbs to the top of a giant beanstalk where he uses his quick wits to outsmart an ogre and make his and his mother's fortune